FINANCIAL RISK: THE INTERPLAY OF LEVERAGE, INTANGIBLES, AND EARNINGS MANAGEMENT - Lumbantobing, Chandra Rony; Iriyadi, Iriyadi; Puspitasari, Ratih; Tullah, Dewi Sarifah; Febrian, Jan (Kesatuan Press, 2025)
Manufacturing companies face financial risks that may lead to financial distress, primarily due to high leverage and the uncertainty of intangible asset values. This study uses earnings management as a moderating variable to investigate how leverage and intangible assets affect financial risk. Using a purposive sample technique, the study uses secondary data from the 2019–2023 financial statements of industrial businesses registered on the Indonesia Stock Exchange (IDX). Data analysis is conducted through panel data regression, employing the Zmijewski model to measure financial risk. The findings reveal that leverage positively affects financial risk, supporting agency theory, which suggests that high debt levels increase financial pressure on firms. In contrast, intangible assets do not significantly influence financial risk. Earnings management reduces financial risk and weakens the impact of leverage, but does not significantly moderate the relationship between intangible assets and financial risk. The study concludes that companies must manage and leverage prudently and optimize using intangible assets to mitigate financial risk. From a practical perspective, investors and creditors should consider earnings management practices when assessing a company's risk profile.